Microbial genetics - Maloy, Stanley R. (Jones and Bartlett Publishers, 1994)
The revision of this classic textbook by David Freifelder has been rewritten and updated to include the numerous and recent advances in microbial genetics. The basic format, organization and style of the first edition has been retained.